Ethnicity as a political resource : conceptualizations across disciplines, regions, and periods (2015)
How is ethnicity viewed by scholars of different academic disciplines? Can its emergences be compared in various regions of the world? How can it be conceptualized with specific reference to distinct historical periods? This book shows in a uniquely and innovative way the broad range of approaches to the political uses of ethnicity, both in contemporary settings and from a historical perspective. Its scope is multidisciplinary and spans across the globe. It is a suitable resource for teaching material. With its short contributions, it conveys central points of how to understand and analyze ethnicity as a political resource.